Endodontic Treatment of a Hypertaurodont Mandibular Second Molar: A Case Report - Janani, Maryam (Iranian Center for Endodontic Research, 2011)
A 28-year old patient was referred for endodontic treatment of his left mandibular second molar. The patient had no history of systemic diseases and his chief complaint was spontaneous pain in left posterior region of mandible. Clinically, there was a deep caries in the left mandibular second molar. Radiographic examination of this tooth revealed a long crown containing large pulp chamber and two short roots with a apically located furcation, indicating hypertaurodontism. After coronal access preparation, five orifices were found including mesiolingual, mesiobuccal, distobuccal, mid-distal and distolingual. Subsequent to root canal preparation, a modified filling technique was used for canal obturation. After one year the treated tooth was symptom free.